2008
DOI: 10.1177/1525740108321217
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Speech and Language Skills of Children With Cochlear Implants and Children With Normal Hearing

Abstract: This study explored the language skills of children with cochlear implants (CIs) compared to normal hearing (NH) peers. Standardized speech and language measures, including speech articulation, receptive and expressive vocabulary, syntax and morphology, and metalinguistics, were administered to 39 congenitally deaf children, ages 5 to 14, and a matched sample of NH children. Many CI children demonstrated age-appropriate scores on several language measures, yet their performance was significantly lower than NH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
80
5
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(95 citation statements)
references
References 39 publications
(50 reference statements)
7
80
5
3
Order By: Relevance
“…Among the components of language, grammatical development seems to be particularly challenging for children with CIs who speak English or other languages (Duchesne, 2015;Duchesne, Sutton, & Bergeron, 2009;Schorr, Roth, & Fox, 2008). In a study by Geers (2004), about 50% of English-speaking children with CIs scored below the typical range on productivity of morphological and syntactic structures in language samples despite having used CIs for an average of 5.5 years.…”
mentioning
confidence: 99%
“…Among the components of language, grammatical development seems to be particularly challenging for children with CIs who speak English or other languages (Duchesne, 2015;Duchesne, Sutton, & Bergeron, 2009;Schorr, Roth, & Fox, 2008). In a study by Geers (2004), about 50% of English-speaking children with CIs scored below the typical range on productivity of morphological and syntactic structures in language samples despite having used CIs for an average of 5.5 years.…”
mentioning
confidence: 99%
“…More recently, several studies have shown that children who have received their cochlear implants at very young ages (and have had several years of experience) can achieve spoken language development at similar rates to children with normal hearing (Connor et al, 2006;Duchesne et al, 2009;Geers, 2006b;Schorr et al, 2008;Svirsky et al, 2004;Tomblin et al, 2005). For example, Dettman et al 2008 reported that children implanted before the age of 2.5 years showed an average vocabulary development rate of 85% of that of children with normal hearing.…”
Section: Language Developmentmentioning
confidence: 99%
“…For children with congenital deafness, a significant correlation between age at implantation and outcomes has also been documented in many recent studies. Children implanted earlier show faster growth of speech perception (Tajudeen et al, 2010;Uziel et al, 2007), language (Connor et al, 2000;Nikolopoulos et al, 2004;Schorr et al, 2008;Tomblin et al, 2005) and reading abilities (Archbold et al, 2008a;Geers et al, 2008;James et al, 2008;Johnson & Goswami, 2010), and also have improved psychosocial outcomes (Schorr, 2006). Development of speech production is also associated with age at implantation, with slower rates of development shown by children who received their implants later (Flipsen, 2008;Peng et al, 2004;Tye-Murray et al, 1995).…”
Section: Age At Implant/duration Of Profound Deafnessmentioning
confidence: 99%
“…Although this trend is positive, a significant number of children who are DHH continue to show delays in language development (Geers, 2004;Geers & Sedey, 2011;Niparko, Tobey, Thal, Eisenberg, Wang, Quittner, & Fink, 2010;Schorr, Roth, & Fox, 2008;Svirsky, Robbins, Kirk, Pisoni, & Miyamoto, 2000). These deficits are particularly evident in advanced language skills such as reading, writing and narrative discourse (Geers, Nicholas, & Sedey, 2003;Spencer, Barker, & Tomblin, 2003).…”
Section: Rationale For the Present Studymentioning
confidence: 99%
“…As we know, in spite of advanced technology, many children who are DHH still show delayed spoken language development when compared to their age-matched peers (Geers, Moog, Biedenstein, Brenner, & Hayes, 2009;Schorr, Roth, & Fox, 2008). These language delays may have a negative impact on the development of EFs in children who are DHH, which in turn has a negative impact on language development because the relationship between language and EFs may be bidirectional (Landa & Goldberg, 2005;Russell, Saltmarsh & Hill, 1999).…”
Section: Children Who Are Dhh Language and Executive Functionsmentioning
confidence: 99%